2006
DOI: 10.1111/j.1365-2613.2006.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of time course changes in inter‐renal aortic banding‐induced left ventricular hypertrophy of mice

Abstract: The left ventricular hypertrophy (LVH) in response to pressure overload is an important risk factor in cardiac morbidity and mortality. To investigate the time course of histopathological alterations in the LVH in response to pressure overload, histopathological and immunohistochemical examination was performed using the aortic banding-induced mouse LVH model. Five-week-old male CD-1 mice were subjected to the inter-renal aortic banding. Major organs were sampled on 3, 10, 14, 21, 28 or 42 days after banding. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…In general, the physiological, morphological, and biochemical alterations with PNx were similar to that which we have reported in the male SpragueDawley rat, where suprarenal aortic constriction was used as a control for hypertensive changes (5). Interestingly, the CD1 mouse also develops severe hypertension with suprarenal aortic constriction but very little cardiac hypertrophy or fibrosis over a similar time course to what we employed in our current study (4,17). Moreover, in the current study, "triple" antihypertensive therapy (15) substantially lowered blood pressure toward normal, but it did not attenuate the cardiac hypertrophy or fibrosis induced by PNx.…”
Section: Discussionsupporting
confidence: 80%
“…In general, the physiological, morphological, and biochemical alterations with PNx were similar to that which we have reported in the male SpragueDawley rat, where suprarenal aortic constriction was used as a control for hypertensive changes (5). Interestingly, the CD1 mouse also develops severe hypertension with suprarenal aortic constriction but very little cardiac hypertrophy or fibrosis over a similar time course to what we employed in our current study (4,17). Moreover, in the current study, "triple" antihypertensive therapy (15) substantially lowered blood pressure toward normal, but it did not attenuate the cardiac hypertrophy or fibrosis induced by PNx.…”
Section: Discussionsupporting
confidence: 80%
“…In AC 2 animals, the expression of this protein was significantly higher than both C and AC 1 . In accordance with recent data obtained in mice with interrenal aortic banding (11,15), the marked increase in SMA expression in long-lasting pressure overload could be mainly attributed to the proliferation/hypertrophy of vascular smooth muscle cells in the media, typical hypertension-related change in resistant vessels including the coronary arteries. Alpha-SMApositive cells in the adventitia and perivascular regions, attributable to differentiation of fibroblasts into myofibroblasts (16), were negligible in both AC groups.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have characterized the inflammatory cell response in pressure overload in young animals [20], [23]. Xia et al demonstrated no significant neutrophil infiltration following TAC and a peak infiltration of macrophages within 2 weeks which subsided by 28 days.…”
Section: Resultsmentioning
confidence: 99%